Changing diets over time: knock-on effects of marine megafauna overexploitation on their competitors in the southwestern Atlantic Ocean. Issue 1 (February 2023) - Bas, Maria; Tivoli, Angélica M.; Briz i Godino, Ivan; Salemme, Mónica; Santiago, Fernando; Belardi, Juan Bautista; Borella, Florencia; Vales, Damián G.; Crespo, Enrique A.; Cardona, Luis
Abstract: This study compares the δ 15 N values and the trophic position of two seabird species throughout the late Holocene in three regions in the southwestern Atlantic Ocean to assess the hypothesis that the decimation of megafauna led to changes in the trophic position of mesopredators. Modern and ancient mollusk shells were also analyzed to account for changes in the isotopic baseline through time. Results revealed that modern Magellanic penguins have higher δ 15 N values than their ancient conspecifics in the three regions, after controlling for changes in the isotopic baseline. This was also true for modern Imperial shags compared with ancient unidentified cormorants/shags from the two areas where ancient specimens were recovered (southern Patagonia and the Beagle Channel). Such temporal variability might be caused by three non–mutually exclusive processes: decreased availability of pelagic squat lobster resulting from decreasing primary productivity through the late Holocene, increased availability of small fishes resulting from the sequential depletion of other piscivores (South American fur seal and sea lion and Argentine hake) since the late eighteenth century, and modification of the migratory patterns of Magellanic penguins. Although disentangling the relative contribution of all those processes is impossible at this time, the results reported here demonstrate that the ecology of Magellanic penguins and Imperial shags has undergone major changes since the late Holocene.